Incidence of pregnancy in feedlot heifers at slaughter - Laudert, S.B. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Nearly 83,000 heifers were observed at slaughter during 1986 and 1987 to determine their reproductive status. Slightly less than 4 percent were found to be pregnant. Highest incidences of pregnancy were found during the winter months of November through March. Lowest incidences were found during August, September. and October.
Keywords: Beef; Pregnant feedlot heifers; Reproduction